PROBLEMATIKA PENERAPAN KURIKULUM MERDEKA DIKELAS IV MIN 9 BANJAR - Karimah, Nurul; Salmah, Syarifah (DARRIS: Jurnal Pendidikan Madrasah Ibtidaiyah, 2024)
Abstract: This research discusses the problems of implementing the independent curriculum in class IV MIN 9 Banjar. The aim of this research is to find out the problems of implementing the independent curriculum in class IV MIN 9 Banjar, to find out what the problems are in implementing the independent curriculum in class IV MIN 9 Banjar and to find out the solutions made by teachers in dealing with the problems of implementing the independent curriculum in class IV MIN 9 Banjar. The subjects in this research were the principal and homeroom teacher of class IV MIN 9 Banjar. Meanwhile, the object studied is the problem of implementing the independent curriculum at MIN 9 Banjar. Data collection techniques in this research used observation, interview and documentation techniques. Meanwhile, data processing techniques are carried out by reducing data, presenting data, drawing conclusions and analyzing data, then analyzing it descriptively qualitatively.Based on the research results, it is known that the implementation of the independent curriculum has been going on for 2 years, the implementation of the curriculum is being carried out in stages for classes I, II, IV and V. Meanwhile classes III and VI will adopt the independent curriculum in the following academic year. The problems felt by teachers in class IV are difficulties in compiling learning tools, choosing the right method, and determining the appropriate type of assessment. Efforts made by teachers to address problems in implementing the independent curriculum in class IV MIN 9 Banjar held meetings with the teacher working group (KKG), attended independent curriculum training, and coordinated with colleagues. Keywords: Implementation, Independent Curriculum, Problematic. Abstrak: Penelitian ini membahas tentang problematika penerapan kurikulum merdeka dikelas IV MIN 9 Banjar. Tujuan dari penelitian ini adalah untuk mengetahui problematika penerapan kurikulum merdeka dikelas IV MIN 9 Banjar, untuk mengetahui apa saja problematika penerapan kurikulum merdeka dikelas IV MIN 9 Banjar dan untuk mengetahui solusi yang dilakukan oleh guru dalam menghadapi problematika penerapan kurikulum merdeka dikelas IV MIN 9 Banjar. Subjek dalam penelitian ini adalah kepala sekolah dan wali kelas IV MIN 9 Banjar. Sedangkan objek yang diteliti adalah problematika penerapan kurikulum merdeka di MIN 9 Banjar. Teknik pengumpulan data dalam penelitian ini menggunakan teknik observasi, wawancara dan dokumentasi. Sedangkan teknik pengolahan data dilakukan dengan reduksi data, penyajian data, menarik kesimpulanan dan analisis data, selanjutnya dianalisis secara deskriptif kualitatif.             Berdasarkan hasil penelitian diketahui bahwa penerapan kurikululum merdeka telah berlangsung selama 2 tahun, implementasi kurikulum tersebut dilaksanakan secara bertahap untuk kelas I, II, IV dan V. sementara kelas III, dan VI akan mengadopsi kurikulum merdeka pada tahun ajaran berikutnya. Problematika yang dirasakan guru di kelas IV yaitu kesulitan dalam menyusun perangkat pembelajaran, memilih metode yang tepat, dan menentukan jenis penilaian yang cocok. Upaya yang dilakukan guru dalam problematika pada penerapan kurikulum merdeka dikelas IV MIN 9 Banjar mengadakan pertemuan dengan kelompok kerja guru (KKG), mengikuti pelatihan kurikulum merdeka, dan berkoordinasi dengan rekan sejawat.Kata Kunci: Kurikulum Merdeka, Penerapan, Problematika.